2006
DOI: 10.1007/s11103-005-4922-z
|View full text |Cite
|
Sign up to set email alerts
|

The Rice OsRad21-4, an Orthologue of Yeast Rec8 Protein, is Required for Efficient Meiosis

Abstract: In yeast, Rad21/Scc1 and its meiotic variant Rec8 are key players in the establishment and subsequent dissolution of sister chromatid cohesion for mitosis and meiosis, respectively, which are essential for chromosome segregation. Unlike yeast, our identification revealed that the rice genome has 4 RAD21-like genes that share lower than 21% identity at polypeptide levels, and each is present as a single copy in this genome. Here we describe our analysis of the function of OsRAD21-4 by RNAi. Western blot analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 66 publications
6
105
0
Order By: Relevance
“…The male meiocytes in OsRAD21-4-deficient lines showed overcondensation of chromosomes, precocious segregation of homologs and chromosome fragmentation. Fluorescence in situ hybridization revealed that OsRAD21-4-deficient lines were defective in homologous pairing and cohesion at sister chromatid arms [45]. These results strongly support a conserved molecular mechanism for male meiosis in monocots and eudicots.…”
Section: Conserved Male Meiosis In Monocots and Eudicotssupporting
confidence: 55%
See 3 more Smart Citations
“…The male meiocytes in OsRAD21-4-deficient lines showed overcondensation of chromosomes, precocious segregation of homologs and chromosome fragmentation. Fluorescence in situ hybridization revealed that OsRAD21-4-deficient lines were defective in homologous pairing and cohesion at sister chromatid arms [45]. These results strongly support a conserved molecular mechanism for male meiosis in monocots and eudicots.…”
Section: Conserved Male Meiosis In Monocots and Eudicotssupporting
confidence: 55%
“…In addition to the conserved sequences and functions of rice SDS and RCK shown in this study, a small number of rice meiosis genes have been studied including PAIR2 [43], OsDMC1 [44], OsRad21-4 [45] and their functions in rice male meiosis are conserved compared to their correspondent homologous genes ASY1 [58], AtDMC1 [59,60], SYN1 [61] in Arabidopsis. In Arabidopsis, the ASY1 protein is localized to the axial/lateral elements and an asy1 mutant is asynaptic and unable to form SC in both male and female meiocytes, indicating its critical role in SC formation [54,58,62].…”
Section: Conserved Male Meiosis In Monocots and Eudicotsmentioning
confidence: 95%
See 2 more Smart Citations
“…Cohesin proteins, which are thought to be involved in this process, have been extensively studied in yeast and animals [4][5][6]. In plants, some cohesin proteins have been characterized for their influence in meiotic pairing, especially the REC8 homologs: SYN1/DIF1 in Arabidopsis [7][8][9], AFD1 in maize [10] and OsRAD21-4 in rice [11]. It is becoming evident that the cohesin complex provides the basis for AE assembly and is implicated in various meiotic events [4,12].…”
Section: Introductionmentioning
confidence: 99%